Thermal analysis of copper-containing oxide systems produced by AC electrochemical oxidation of metals; International Conference on Thermal Analysis and Calorimetry in Russia (RTAC-2016); Vol. 1 - Usoltseva N. V. Natalia Vasilievna (Section 1: Thermal analysis and calorimetry of inorganic substances and materials, 2016)
The products of AC electrochemical oxidation of metals were characterized by DSC/DTG analysis. Individual copper oxidation and joint oxidation of copper and aluminum / cadmium was carried out in sodium chloride. Copper oxide (I) which is formed by AC copper oxidation is oxidized to copper oxide (II) at 260 °C. The product of joint oxidation of copper and aluminum consists of copper oxide (I) and aluminum oxyhydroxide (Cu2O, AlOOH). At joint oxidation of copper and cadmium the oxides and hydroxides of copper and cadmium (γ-Cd(OH)2, Cu(OH)2, β-Cd(OH)2, CdO and Cu2O) are formed. Joint AC oxidation with aluminium does not affect the temperature of Cu2O oxidation whereas electrolysis with cadmium causes the temperature increate to 320°C.